Uncovering a conserved vulnerability site in SARS‐CoV‐2 by a human antibody. Issue 12 (17th November 2021) - Li, Tingting; Cai, Hongmin; Zhao, Yapei; Li, Yanfang; Lai, Yanling; Yao, Hebang; Liu, Liu Daisy; Sun, Zhou; van Vlissingen, Martje Fentener; Kuiken, Thijs; GeurtsvanKessel, Corine H; Zhang, Ning; et al.
Abstract: An essential step for SARS‐CoV‐2 infection is the attachment to the host cell receptor by its Spike receptor‐binding domain (RBD). Most of the existing RBD‐targeting neutralizing antibodies block the receptor‐binding motif (RBM), a mutable region with the potential to generate neutralization escape mutants. Here, we isolated and structurally characterized a non‐RBM‐targeting monoclonal antibody (FD20) from convalescent patients. FD20 engages the RBD at an epitope distal to the RBM with a K D of 5.6 nM, neutralizes SARS‐CoV‐2 including the current Variants of Concern such as B.1.1.7, B.1.351, P.1, and B.1.617.2 (Delta), displays modest cross‐reactivity against SARS‐CoV, and reduces viral replication in hamsters. The epitope coincides with a predicted "ideal" vulnerability site with high functional and structural constraints. Mutation of the residues of the conserved epitope variably affects FD20‐binding but confers little or no resistance to neutralization. Finally, in vitro mode‐of‐action characterization and negative‐stain electron microscopy suggest a neutralization mechanism by which FD20 destructs the Spike. Our results reveal a conserved vulnerability site in the SARS‐CoV‐2 Spike for the development of potential antiviral drugs. SYNOPSIS: A monoclonal antibody (FD20) from convalescent COVID‐19 patients has been isolated and structurally and biologically characterized. Various SARS‐CoV‐2 strains, including the Alpha, Beta, Gamma, and Delta variants, and naturally occurring epitope mutants, can be neutralized by FD20 with similar potency. A broadly active mAb is identified with consistent neutralizing activity against 14 SARS‐CoV‐2 strains/mutants and weak activity against SARS‐CoV. The conservation of FD20's epitope residues is supported by their low mutation frequencies both in nature and in laboratory experiments. A neutralizing mechanism through which the surface glycoprotein is destructed by FD20 is proposed based on electron microscopy evidence. Abstract : A monoclonal antibody (FD20) from convalescent COVID‐19 patients has been isolated and structurally and biologically characterized. Various SARS‐CoV‐2 strains, including the Alpha, Beta, Gamma, and Delta variants, and naturally occurring epitope mutants, can be neutralized by FD20 with similar potency.